IMPLEMENTASI PRINSIP-PRINSIP MANAJEMEN PENDIDIKAN ISLAM: STUDI KASUS MADRASAH IBTIDAIYAH “AL-MUKMININ” KALANGAN, JOMBANG - Ririn Rosdiarini (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
Education management, including madrasas, is undergoing a fundamental change, especially in terms of paradigm it develops, i.e. applying bottom up management concepts with a primary focus on efforts to improve quality through autonomy, accountability, accreditation, and evaluation. This new paradigm is basically used to arouse motivation and to launch systems based on merit, transparency, and public accountability. Madrasa, as an Islamic educational institution, in addition to aligning themselves with changes in aspects of the management paradigm as mentioned above also still maintain its characteristics. This characteristic distinguishes between madrasas and general educational institutions. One such distinction is the application of management principles derived from the great sources of Islamic teachings, namely the Qur’an and Hadith. Using a qualitative approach and descriptive-analytical method, this study describes the application of the principles of Islamic education management by taking the locus of research at MI “Al-Mukminin” Kalangan Perak, Jombang Regency. This study tries to examine the extent to which this institution applies the principles of Islamic education management which includes such principles as shura, ikhlas, sidq, amanah, and taqwa. Based on data, which was explored in depth through interviews and observations, the study finds that MI “Al-Mukminin” has properly applied the principles of Islamic education management. In addition, the application of these principles is also in accordance with the vision, mission, and objectives of the madrasa.